Optimization and Experimental Testing of the Drag Torque Model Based on the Cavitation Effect - Li Jie; Lian Hailong; Lan Hai; Wang Zhiyong (Jixie chuandong)
In the non-braking operation of the wet brake in a heavy vehicle's hybrid power transmission system, the friction pair produces a drag torque due to the power loss caused by the viscous action of the oil. In order to realize the accurate prediction of the drag torque of the flow field with the complex trench structure, a method is proposed to optimize the drag torque model by predicting the volume fraction of the cavitation effect through the cavitation number aiming for the prediction error caused by the air entering the flow field in advance. Firstly, the influence of rotation speed, flow rate and clearance on the volume fraction of the cavitation effect is analyzed by calculating the model under different working conditions. With the increased rotation speed, the cavitation effect volume fraction increases first and then decreases. Larger flow rates and smaller gaps will increase the maximum value of the cavitation effect volume fraction. Then, the wet brake drag torque is tested. After comparative analysis, the results show that the prediction error of the optimized model is less than 6%, and the average error is reduced by 55% compared with the model without the cavitation effect. In addition, the influence of the complexity of the trench structure on the drag torque is also studied. It is shown that the more complex the trench structure is, the smaller the drag torque is, and the radial trench has the most significant influence on the drag torque, which reduces the drag torque by nearly 25.9%. It provides support and engineering practice guidance for accurately predicting the drag torque and optimizing the friction plate structure of wet brakes.